2002
DOI: 10.1074/jbc.m204610200
|View full text |Cite
|
Sign up to set email alerts
|

Janus Kinase 2, an Early Target of α7 Nicotinic Acetylcholine Receptor-mediated Neuroprotection against Aβ-(1–42) Amyloid

Abstract: The molecular mechanisms of ␣7 nicotinic acetylcholine receptor (nAChR)-mediated neuroprotection remain unclear. In this study we provide evidence that nicotine stimulation of ␣7 nAChR transduces signals to phosphatidylinositol 3-kinase and Akt via Janus kinase 2 (JAK2) in a cascade, which results in neuroprotection. Exposure to ␤-amyloid results in the activation of the apoptotic enzyme caspase-3 and cleavage of the DNA-repairing enzyme poly-(ADP-ribose) polymerase. This cascade is inhibited by nicotine throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
157
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(166 citation statements)
references
References 21 publications
7
157
1
1
Order By: Relevance
“…In the neuronal cell line PC12, nicotine competes with Aβ42 for the binding to alpha7nAChR (in a "dominant" way), and prevents the Aβ42-induction of caspase 3 and apoptosis. The latter seems to be the result of nicotinic activation of the JAK2-PI3K-Akt signalling pathway, rather than blockade of Aβ42 binding to the alpha7nAChR (Shaw et al, 2002). This effect appears to be mediated by alpha7nAChR because the protection is blocked by alpha-bungarotoxin and is mimicked by the alpha7nAChR-agonist TC-1698 (Marrero et al, 2004;Shaw et al, 2002Shaw et al, , 2003.…”
Section: Alpha7nachr Neurotoxicity and Neuroprotectionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the neuronal cell line PC12, nicotine competes with Aβ42 for the binding to alpha7nAChR (in a "dominant" way), and prevents the Aβ42-induction of caspase 3 and apoptosis. The latter seems to be the result of nicotinic activation of the JAK2-PI3K-Akt signalling pathway, rather than blockade of Aβ42 binding to the alpha7nAChR (Shaw et al, 2002). This effect appears to be mediated by alpha7nAChR because the protection is blocked by alpha-bungarotoxin and is mimicked by the alpha7nAChR-agonist TC-1698 (Marrero et al, 2004;Shaw et al, 2002Shaw et al, , 2003.…”
Section: Alpha7nachr Neurotoxicity and Neuroprotectionmentioning
confidence: 98%
“…The latter seems to be the result of nicotinic activation of the JAK2-PI3K-Akt signalling pathway, rather than blockade of Aβ42 binding to the alpha7nAChR (Shaw et al, 2002). This effect appears to be mediated by alpha7nAChR because the protection is blocked by alpha-bungarotoxin and is mimicked by the alpha7nAChR-agonist TC-1698 (Marrero et al, 2004;Shaw et al, 2002Shaw et al, , 2003. Treatment with nicotine for ten days in the APPsw mice model (transgenic mice overproducing mutant amyloid β protein precursor, βAPP) reduced insoluble amyloid Aβ1-40 and Aβ1-42 peptides by 80% in the brain cortex of 9 month-old mice (Hellstrom-Lindahl et al, 2004a).…”
Section: Alpha7nachr Neurotoxicity and Neuroprotectionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,52) Activation of Akt in turn increases the expression level of Bcl-2 transcript. We observed that treatment with donepezil and galantamine, but not tacrine, also increases the phosphorylation level of Akt and the expression level of Bcl-2 transcript.…”
Section: Mechanism Of Acetylcholinesterase In-hibitor-induced Neuroprmentioning
confidence: 99%
“…31,52) With the involvement of nAChR in acetylcholinesterase inhibitor-induced neuroprotection, we examined the involvement of this pathway in acetylcholinesterase inhibitor-induced neuroprotection. Treatment with PP2, AG490, LY294002 and wortmannin, inhibitors of Fyn, JAK2 and PI3K, respectively, significantly inhibited neuroprotection by donepezil and galantamine, but not tacrine, which is in good accordance with the results of MLA treatment described above.…”
Section: Mechanism Of Acetylcholinesterase In-hibitor-induced Neuroprmentioning
confidence: 99%